To the manor born: a new microlevel wage database for eighteenth-century Denmark. (9th August 2021) - Jensen, Peter Sandholt; Radu, Cristina Victoria; Sharp, Paul
Abstract: We document and make available to the scholarly community a uniquely detailed database of 20, 680 observations of wages for men, women, and children and 30, 000 observations of prices from eighteenth-century rural Denmark. These microlevel data were originally collected by the Danish Price History Project but have not previously been released. To illustrate the usefulness of such data, we discuss possible applications.